Morphological traits predict host-tree specialization in wood-inhabiting fungal communities. (August 2020) - Purhonen, Jenna; Ovaskainen, Otso; Halme, Panu; Komonen, Atte; Huhtinen, Seppo; Kotiranta, Heikki; Læssøe, Thomas; Abrego, Nerea
Abstract: Tree species is one of the most important determinants of wood-inhabiting fungal community composition, yet its relationship with fungal reproductive and dispersal traits remains poorly understood. We studied fungal communities (total of 657 species) inhabiting broadleaved and coniferous dead wood (total of 192 logs) in 12 semi-natural boreal forests. We utilized a trait-based hierarchical joint species distribution model to examine how the relationship between dead wood quality and species occurrence correlates with reproductive and dispersal morphological traits. Broadleaved trees had higher species richness than conifers, due to discomycetoids and pyrenomycetoids specializing in them. Resupinate and pileate species were generally specialized in coniferous dead wood. Fungi inhabiting broadleaved trees had larger and more elongated spores than fungi in conifers. Spore size was larger and spore shape more spherical in species occupying large dead wood units. These results indicate the selective effect of dead wood quality, visible not only in species diversity, but also in reproductive and dispersal traits. Highlights: Broadleaved dead wood had higher fungal species richness than coniferous dead wood. Discomycetoids and pyrenomycetoids specialized on broadleaved dead wood. Resupinate and pileate species specialized on coniferous dead wood. Broadleaved trees had species with larger and more elongated spores than conifers. Spore size was larger and shape more spherical in species occupying larger dead wood.